Macdentichalcone, a unique polycyclic dimeric chalcone from Macaranga denticulata. Issue 49 (7th December 2016) - Lei, Chun; Zhang, Lai-Bin; Yang, Jing; Gao, Li-Xin; Li, Jing-Ya; Li, Jia; Hou, Ai-Jun
Graphical abstract: Highlights: Macdentichalcone (1 ) is an unprecedented polycyclic dimeric chalcone. Both1 and its proposed biosynthetic precursor2 showed PTP1B inhibition. The structure of1 was established by extensive NMR methods and 13 C NMR calculation. Abstract: Macdentichalcone (1 ), an unprecedented polycyclic dimeric chalcone featuring a unique quinonoid moiety, was isolated from Macaranga denticulata, together with 1-(5, 7-dihydroxy-2, 2, 6-trimethyl-2 H -1-benzopyran-8-yl)-3-phenyl-2-propen-1-one (2 ), a known monomeric chalcone proposed as a biosynthetic precursor of1 . The structure of1 was elucidated by extensive spectroscopic analysis including NMR and MS data, as well as calculation of 13 C NMR chemical shifts. Both compounds1 and2 showed inhibitory activity against PTP1B in vitro .